La apologética antijudía de Juan Luis Vives (1543) - Vincent Parello (Mélanges de la Casa de Velázquez, 2008)
In his apologia entitled De veritate fidei christianae (On the truth of the Christian Faith), Juan Luis Vives sought to achieve a synthesis between Judaism and Christianity, the latter conceived as a spiritual form of Judaism. Through the teachings of Thomist theology, the Bible, Aristotelianism and philological science, Vives sought to apply intelligence, God’s supreme gift to man, to the study –or rather the textual criticism– of the Holy Scriptures.